2021
DOI: 10.1002/pits.22543
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the four walls: The evolution of school psychological services during the COVID‐19 outbreak

Abstract: The emergence of the novel coronavirus disease (COVID‐19) in early 2020 led to the sudden temporary closure of K‐12 schools across the United States. Schools were tasked with providing remote instruction to students, and many of these children continued to require mental and behavioral health services provided by school psychologists. In this study, 675 school psychologists were surveyed across the United States to examine how their roles and responsibilities changed as a result of COVID‐19. Participants repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 35 publications
(81 reference statements)
6
31
0
3
Order By: Relevance
“…This finding, in a way, seems to be confirmed by the literature where it is mentioned that the provision of socio-emotional support to fellow teachers is a degraded task of the psychologist [29,56]. However, in a study of the role of the school psychologist in the COVID-19 era [44], the role of teachers' support on their own personal problems seemed to emerge significantly.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This finding, in a way, seems to be confirmed by the literature where it is mentioned that the provision of socio-emotional support to fellow teachers is a degraded task of the psychologist [29,56]. However, in a study of the role of the school psychologist in the COVID-19 era [44], the role of teachers' support on their own personal problems seemed to emerge significantly.…”
Section: Discussionsupporting
confidence: 61%
“…Apparently, as a result of the first wave of the COVID-19 pandemic, schools' psychological support services have been rapidly transformed around the world to accommodate the need for prolonged physical distancing [44]. A variety of coping strategies have emerged in an attempt to continue to support children, including providing distance learning, online counseling, and various hybrid support configurations, involving both in-person and remote strategies [40].…”
Section: The Emerging Role Of the School Psychologist In The Covid-19 Eramentioning
confidence: 99%
“…The online survey employed for this study was initially developed by the research team in the United States (Schaffer et al, 2021), and modified for the present study with permission from the authors. Research teams from each of the other participating countries adapted the original survey to align with their specific circumstances, with a core set of survey items based on the research aims consistent across all four countries.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps not surprisingly, Schaffer et al (2021) found that during school closures, 98.3% of psychologists working in schools in the United States indicated that they were not required to administer standardized psychoeducational assessments remotely. Instead, they engaged in other services that could be delivered virtually, including consultation, counseling, and developing interventions and supports for teachers and parents (Schaffer et al, 2021). It is unclear how psychologists working in schools in other parts of the world responded to school closures nor how responses across countries may differ.…”
Section: Covid-19 and School Psychology Servicesmentioning
confidence: 99%
“…Previous studies demonstrated that school psychology practice changed during school closures. In a survey completed by 675 US school psychologists, Schaffer et al (2021) reported a shift in responsibilities, from being predominately assessment focused (for special education eligibility) to being more consultative and collaborative with teachers and parents. The shift appeared to occur due to problems associated with conducting virtual assessments with students.…”
mentioning
confidence: 99%